Synthetic aperture radar image process and analysis - Wen, Bihan (2013)
ASAR (Advanced Synthetic Aperture Radar) is a form of radar in which multiple radar images are processed to yield higher-resolution images. ASAR is an all-weather, day-and-night, high-resolution imaging instrument carried by EnviSat. Why do we need a new ASAR image processing software? The traditional ASAR image tool named EnviView is only capable of decoding EnviSat data file. However, this manner of data processing gives rise to inconvenience of user operations such as free zoom, pseudocolor transformation and image enhancement. Hence, a user friendly ASAR data viewing software is needed to ease the ASAR image analysis. RadarImageStudio is the ASAR image analyzing software based on MATLAB. It fully satisfies these needs and provides simple GUI and use simplicity for users. [2nd Award]